2020
DOI: 10.12659/msm.924832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2D-Shear Wave Elastography on Brain-Derived Neurotrophic Factor (BDNF) in the Brains of Neonatal Mice and Exploration of the Mechanism

Abstract: Background: The aim of this study was to explore the effect and duration of 2-dimensional shear wave elastography (2D-SWE) irradiation on the expression of brain-derived neurotrophic factor (BDNF) in the brains of neonatal mice and to preliminarily investigate whether its mechanism is neuronal apoptosis. Material/Methods: Neonatal mice (within 48 hours of birth) were subjected to 2D-SWE irradiation of the brain for 10 minutes (group S1), 20 minutes (group S2), and 30 minutes (group S3). The mice were sacrifice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The authors found that SWE irradiation for more than 10 min temporarily downregulated the expression of BDNF, although such effect disappeared within 24 h after exposure. Moreover, SWE did not significantly affect the number of apoptotic neurons [33]. Taken together, these data support the good safety profile of neonatal brain elastography, with no reported long-term side effects.…”
Section: Brain Elastography In the Neonatal Settingsupporting
confidence: 76%
See 1 more Smart Citation
“…The authors found that SWE irradiation for more than 10 min temporarily downregulated the expression of BDNF, although such effect disappeared within 24 h after exposure. Moreover, SWE did not significantly affect the number of apoptotic neurons [33]. Taken together, these data support the good safety profile of neonatal brain elastography, with no reported long-term side effects.…”
Section: Brain Elastography In the Neonatal Settingsupporting
confidence: 76%
“…Taken together, these data support the good safety profile of neonatal brain elastography, with no reported long-term side effects. Nevertheless, considering the differences between mice and human neonates in terms of brain volume and skull hardness, studies investigating whether such biologic effects are confirmed in humans are required, and brain elastography should be used cautiously and with minimal exposure time [33].…”
Section: Brain Elastography In the Neonatal Settingmentioning
confidence: 99%